Análise genotóxica e histopatológica do efeito carcinogênico gástrico da exposição ao MNU em primatas Cebus Apella da Amazônia brasileira - GOMES, Amanda Raquel da Silva (2022)
Gastric cancer currently represents a challenge to public health in Brazil, especially in the state of Para, where the mortality due to this cancer, is above the national average. Carcinogenesis is defined as a process of progressive damage to genetic material, leading to irreversible tissue adaptation that culminates in malignant degeneration. Numerous intrinsic and extrinsic conditions are involved in this transformation. For the gastric cancer is well documented infection by H. Pylori, however, given the importance of the subject, several study methods have been proposed in order to understand the intricate process of carcinogenesis and enhance knowledge of the etiopathogenesis of gastric tumor. Win particularly important animal models of chemical carcinogenesis and molecular tests that detect early changes in the genetic material. Among the chemicals used in these models is the N-Methyl-nitrosourea, and other components nitrous known carcinogens as direct. This work aimed to study the genotoxic effects and pathological intake of MNU by Cebus apella, because, despite the remarkable frequency of this species in the Brazilian fauna, the same had not been done. We used the Comet assay and Micronucleus test for toxic DNA analysis of blood cells and gastric tissue, and histopathology of the gastric mucosa of animals. Our results indicate that in a short time, the dose of MNU was used is capable of causing genotoxicity and cumulative damage to genetic material, however, no significant histopathological changes, indicating that the changes continued and cumulative DNA preceding the outbreak tissue. In addition, Cebus apella showed a good potential for reproduction of this type of study because its large regional availability and easy handling combined with a greater sensitivity to low concentrations of MNU, allow for the induction of chemical carcinogenesis more quickly and with a dose less of the drug.